Summer pruning in Mediterranean vineyards: is climate change affecting its perception, modalities, and effects? - Poni, Stefano; Frioni, Tommaso; Gatti, Matteo (Frontiers in Plant Science, 2023)
Abstract: Summer pruning encompasses a series of operations typically performed on the grapevine during the growing season. This review provides an update on the research conducted over the last 20 years on the modalities and strategies of main summer pruning operations, which include shoot positioning and thinning, shoot trimming, leaf removal, and cluster thinning, with a special focus on their adaptation to climate change occurring in Mediterranean areas. Three main novelties emerged from the survey. First, due to a common need to shelter clusters against overheating and sunburn-related damages, shoot thinning and leaf removal are practices that are now being applied in a much more cautious and conservative manner. Second, the meaning of summer pruning is evolving because operations are being used as precious tools to direct ripening toward a desired direction rather than being received passively. Third, some operations, such as leaf removal, have disclosed very high plasticity, which means that, depending on the timing and modalities of the intervention, yield can be either increased or decreased and ripening anticipated or postponed. In an era where economic sustainability and environmental sustainability have to find a good compromise, cluster thinning is increasingly being depicted as an extraordinary operation that should be left to occasional occurrences of overcropping. Moreover, summer pruning is a tool through which growers can, to an extent, exploit the potentialities offered by climate change. For instance, the crop-forcing technique, under the different configurations of single and double cropping within the same season, has been trialed promisingly in several regions and cultivars. The principle of forcing is to unlock the dormant bud during the first year by removing at least the young organs present on the shoot within a time window between the end of the flowering and pea-size stages. In particular, when it is applied in a double-cropping mode, the preliminary results related to Pinot noir, Grenache, Tempranillo, and Maturana tinta indicate that two harvests separated by 30–50 days can be obtained, with the latter having superior quality in terms of a lower level of pH and higher levels of acidity, anthocyanins, and phenolics.